Association between NFKB1 −94ins/del ATTG Promoter Polymorphism and Cancer Susceptibility: An Updated Meta-Analysis. (7th May 2014) - Yang, Xiao; Li, Pengchao; Tao, Jun; Qin, Chao; Cao, Qiang; Gu, Jinbao; Deng, Xiaheng; Wang, Jun; Liu, Xuzhong; Wang, Zijie; Wu, Bian; Gu, Min; et al.
Abstract : Nuclear factor- κ B is associated with the pathogenesis of numerous malignancies, and the functional polymorphism −94ins/del ATTG (rs28362491) in the human NFKB1 gene is associated with cancer risk. Previous studies on the association between the −94ins/del ATTG polymorphism and cancer risk reported conflicting results. To clarify this relationship, we performed a meta-analysis of 21 case-control studies involving 6127 cases and 9238 controls. We used pooled odds ratios (ORs) with their 95% confidence intervals (95% CIs) to assess the association. We found that the NFKB1 promoter −94ins/del ATTG polymorphism was significantly associated with cancer risk in four genetic models (ins/ins versus del/del, OR = 1.47, 95% CI = 1.11–1.93; dominant model, OR = 1.26, 95% CI = 1.03–1.53; recessive model, OR = 1.26, 95% CI = 1.05–1.51; ins allele versus del allele, OR = 1.19, 95% CI = 1.05–1.35). Stratified analyses revealed a significant association between the polymorphism and ovarian, oral, and prostate cancers. Similar results were determined in an Asian population and not in a Caucasian population. Thus, our results suggested that the polymorphism can contribute to cancer risk. Moreover, the polymorphism can exert race- and cancer-specific effects on cancer risk. Further large-scale and functional studies are necessary to elucidate this possible effect.